2021
DOI: 10.30970/sbi.1502.653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thiazole derivative complexed with nanoscale polymeric carriers on cellular ultrastructure of murine lymphoma cells in vivo

Abstract: Background. A pronounced cytotoxic action of the thiazole derivatives complexed with polymeric carriers on tumor cells in vitro was reported earlier, while no cytotoxicity of these compounds was detected toward noncancerous cells. It was found that thiazole derivatives at concentrations of 10 and 50 µM affected lymphoma cell ultrastructure in vitro. The purpose of this work was to investigate the effect of thiazole derivative 8-methyl-2-Me-7-[trifluoromethyl-phenylmethyl]-pyrazolo-[4,3-e]-[1,3]- thiazolo-[3,2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…As is known, polymeric carriers improve the delivery of chemical compounds to the cell. Earlier, it was shown that a 2-amino-5-benzylthiazole derivative in a complex with a PEG-containing carrier (Popovych et al, 2021) did not impair the effect of antineoplastic compounds on lymphoma cells, but caused the lymphoma cells death through apoptotic changes. As C. Yang, H.-Z.…”
Section: Resultsmentioning
confidence: 99%
“…As is known, polymeric carriers improve the delivery of chemical compounds to the cell. Earlier, it was shown that a 2-amino-5-benzylthiazole derivative in a complex with a PEG-containing carrier (Popovych et al, 2021) did not impair the effect of antineoplastic compounds on lymphoma cells, but caused the lymphoma cells death through apoptotic changes. As C. Yang, H.-Z.…”
Section: Resultsmentioning
confidence: 99%
“…PEG-based polymeric nanoparticles (PEG-PNs) may conjugate with many therapeutic anticancer agents increasing solubility and blood-circulation time of antitumor che mi cals, improving targeted delivery to tumor tissues, decreasing side effects on healthy cells, and, as a result, these nanoparticles improve the efficacy of drugs [5,6]. It was established, that combination of BF1 with the polymeric carriers based on polyethylene glycol (PEG) increases the cytotoxicity towards several tumor cell lines [7], causing the apoptotic-like alterations in the mice Nemeth-Kellner lymphoma (NK/Ly) cells [8] and increasing the level of superoxide dismutase (SOD), one of the most important enzyme of the antioxidant defense system [9].…”
Section: Introductionmentioning
confidence: 99%